Genetic Regulation of N6-Methyladenosine-RNA in Mammalian Gametogenesis and Embryonic Development - Chang, Yuguang; Yi, Mingliang; Wang, Jing; Cao, Zhikun; Zhou, Tingting; Ge, Wei; Muhammad, Zafir; Zhang, Zijun; Feng, Yanqin; Yan, Zihui; Felici, Massimo De; Shen, Wei; et al. (Frontiers in Cell and Developmental Biology, 2022)
Emerging evidence shows that m6A is the most abundant modification in eukaryotic RNA molecules. It has only recently been found that this epigenetic modification plays an important role in many physiological and pathological processes, such as cell fate commitment, immune response, obesity, tumorigenesis, and relevant for the present review, gametogenesis. Notably the RNA metabolism process mediated by m6A is controlled and regulated by a series of proteins termed writers, readers and erasers that are highly expressed in germ cells and somatic cells of gonads. Here, we review and discuss the expression and the functional emerging roles of m6A in gametogenesis and early embryogenesis of mammals. Besides updated references about such new topics, readers might find in the present work inspiration and clues to elucidate epigenetic molecular mechanisms of reproductive dysfunction and perspectives for future research.